Oltre gli stereotipi La ricerca-azione di Renzo Rastrelli sull'immigrazione cinese in Italia - Becucci, Stefano (Studi e saggi, 2018)
This volume collects a series of writings by Renzo Rastrelli (1948-2008), a long-time professor of Political and diplomatic history of East Asia at the Faculty of Political Sciences "Cesare Alfieri" of the University of Florence. This textual anthology highlights some of the main aspects of the author's scientific work: the analysis on Chinese immigration to Italy, going beyond common stereotypes; the internal dynamics regarding the associative modalities and the forms of dialogue which the Chinese communities have with Italian society; finally, the broader social context which Chinese immigrants find themselves in, drawing attention to the interlacement of restrictive immigration regulations and the facilitation of illegal practices, involving both Chinese and Italian citizens.